Evaluasi Pelaksanaan Program Ruang Publik terpadu Ramah Anak Mawar di Jakarta Barat - Rafi, Maulana (PUBLICNESS: Journal of Public Administration Studies, 2023)
Children as Indonesian citizens have the right to live a decent life and fulfill their needs and interests. The needs and interests of Indonesian children are regulated in the Regulation of the State Minister for Women's Empowerment and Child Protection No. 12 of 2011. As an effort to carry out the Minister of Women's Empowerment and Child Protection No. 12 of 2011, the Provincial Government of DKI Jakarta built child-friendly integrated public spaces (RPTRA) in several areas of Jakarta. According to Governor Regulation Number 123 of 2017 concerning Guidelines for the Management and Needs of Child-friendly Integrated Public Spaces and Infrastructure, it is stated that child-friendly integrated public spaces, hereinafter abbreviated as RPTRA, are places and/or open spaces that combine activities and activities of residents by implementing 10 (ten ) Main Program for Family Empowerment and Welfare, to integrate with the Child Friendly City program. Now more than 300 RPTRAs have been built in DKI Jakarta. The RPTRA which is built on a park adds to the problem, because there are no criteria and standards that regulate the design of the RPTRA, so the various facilities and elements in the RTPRA have not been specifically designed for children, and may even be dangerous for children. Qualitative research methods are used to determine the implementation of RPTRA as a child-friendly space, especially at RPTRA Mawar Duri Kosambi West Jakarta.